The Problem with Suing Sovereigns: Sloman (1876) - McLay, Geoff (Victoria University of Wellington Law Review, 2010)
In Sloman v The Governor and Government of New Zealand the plaintiff attempted to sue the New Zealand Government for failing to make good on emigration contracts concluded in Europe. This article analyses the decision in Sloman, that the New Zealand government could not be sued in English courts, both within its own historical context and with respect to 19th century concerns over the general inability of the Crown to be sued. The article points to archival documents which show that the New Zealand Government itself was concerned, in the wake of the earlier loss of the Cospatrick, as to its own ability to recover the passage monies it had paid, and whether that recovery might be prevented by a lack of legal personality in the English Courts. The article concludes that while Sloman is an important case in its own right, there is also a need for greater investigation of both the practical and theoretical legal difficulties that faced the New Zealand Government in its development and immigration projects of the 1870s.